Effects of the perinatal environment on the central dopamine system and body weight gain in obesity-prone rats. - Geiger, Brenda. (2017)
Abstract: Obesity, which develops as the result of increased energy intake and/or decreased energy expenditure, has rapidly become one of the largest public health concerns in the world. The explosive prevalence of the obesity epidemic challenges the notion that a homeostatic system of energy balance is in complete control of body weight regulation. The central reward system, particularly the midbrain dopamine pathways, mediates the hedonic value of palatable food and may override the homeostatic control of energy balance. In this work, we use a multi-level approach that includes in vivo microdialysis and behavioral studies, ex vivo slice electrophysiology measurements of stimulated dopamine release, and cellular measurements of mRNA and protein expression to study the influence of dopamine on the development of obesity in inbred obesity-prone (OP) rats. In female animals that are dietary obese or obesity prone, we show decreases of approximately 50% in electrically stimulated dopamine release. These significant deficits in dopamine signaling are linked to decreased sensitivity to amphetamine injections. In the obesity-prone animals, we have also established deficits in tyrosine hydroxylase (TH) and vesicular monoamine transporter-2 (VMAT2) mRNA and protein expression. Obesity-resistant (OR) females that have been exposed to an obesogenic prenatal environment through embryonic transplantation on day E1 to obesity-prone dames show similar deficits in central dopamine neurotransmission that are linked to accelerated body weight gain and decreased spontaneous activity during the pre-pubescent period. Dopamine replacement in obesity-prone females during this period results in a decrease of approximately 10% of both food intake and body weight and more than twice as much stimulated dopamine release in the nucleus accumbens than in obesity-prone control animals. In conclusion depressed dopamine release can be induced by exposure to an obesogenic environment during the prenatal period. Sustained deficits in dopamine during the pre-pubescent period may lead dietary obese and obesity-prone animals to compensate by overeating, particularly palatable food. Selective targeting to increase the synthesis and activity of presynaptic regulators of the mesolimbic dopamine system during this period constitutes a promising approach for both the prevention and treatment of dietary obesity in offspring that are otherwise prone to developing obesity.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisor: Emmanuel Pothos.; Committee: Margery Beinfeld, Martin Beinborn, and Efi Kokkotou.; Keyword: Pharmacology.